Pharmacodynamic evaluation of lefamulin in the treatment of gonorrhea using a hollow fiber infection model simulating Neisseria gonorrhoeae infections - Jacobsson, Susanne; Golparian, Daniel; Oxelbark, Joakim; Wicha, Wolfgang W.; da Costa, Renata Maria Augusto; Franceschi, Francois; Brown, David; Louie, Arnold; Gelone, Steven P.; Drusano, George; Unemo, Magnus (Frontiers in pharmacology, 2022)
The emergence and spread of antimicrobial resistance in Neisseria gonorrhoeae is seriously threatening the treatment and control of gonorrhea globally. Novel treatment options are essential, coupled with appropriate methods to pharmacodynamically examine the efficacy and resistance emergence of these novel drugs. Herein, we used our dynamic in vitro hollow fiber infection model (HFIM) to evaluate protein-unbound lefamulin, a semisynthetic pleuromutilin, against N. gonorrhoeae . Dose–range and dose–fractionation experiments with N. gonorrhoeae reference strains: WHO F (susceptible to all relevant antimicrobials), WHO X (extensively drug-resistant, including ceftriaxone resistance), and WHO V (high-level azithromycin resistant, and highest gonococcal MIC of lefamulin (2 mg/l) reported), were performed to examine lefamulin gonococcal killing and resistance development during treatment. The dose–range experiments, simulating a single oral dose of lefamulin based on human plasma concentrations, indicated that ≥1.2 g, ≥2.8 g, and ≥9.6 g of lefamulin were required to eradicate WHO F, X, and V, respectively. Dose–fractionation experiments, based on human lefamulin plasma concentrations, showed that WHO X was eradicated with ≥2.8 g per day when administered as q12 h (1.4 g twice a day) and with ≥3.6 g per day when administered as q8 h (1.2 g thrice a day), both for 7 days. However, when simulating the treatment with 5–10 times higher concentrations of free lefamulin in relevant gonorrhea tissues (based on urogenital tissues in a rat model), 600 mg every 12 h for 5 days (approved oral treatment for community-acquired bacterial pneumonia) eradicated all strains, and no lefamulin resistance emerged in the successful treatment arms. In many arms failing single or multiple dose treatments for WHO X, lefamulin-resistant mutants (MIC = 2 mg/l), containing an A132V amino acid substitution in ribosomal protein L3, were selected. Nevertheless, these lefamulin-resistant mutants demonstrated an impaired biofitness. In conclusion, a clinical study is warranted to elucidate the clinical potential of lefamulin as a treatment option for uncomplicated gonorrhea (as well as several other bacterial STIs).